2015
DOI: 10.1097/aln.0000000000000749
|View full text |Cite
|
Sign up to set email alerts
|

Increased Noradrenergic Neurotransmission to a Pain Facilitatory Area of the Brain Is Implicated in Facilitation of Chronic Pain

Abstract: Chronic pain induces brainstem noradrenergic activation that enhances descending facilitation from the DRt. This suggests that antidepressants inhibiting noradrenaline reuptake may enhance pain facilitation from the brain, counteracting their analgesic effects at the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 54 publications
4
44
0
1
Order By: Relevance
“…This implies the LC is a chronic pain generator. The results also concur with studies implying that with persisting trigeminal nociceptive input, the LC contributes to facilitation of mechanical hypersensitivity through both descending and ascending circuitry (Martins, et al, 2013; Martins et al, 2015). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This implies the LC is a chronic pain generator. The results also concur with studies implying that with persisting trigeminal nociceptive input, the LC contributes to facilitation of mechanical hypersensitivity through both descending and ascending circuitry (Martins, et al, 2013; Martins et al, 2015). …”
Section: Discussionsupporting
confidence: 89%
“…LC neuronal activation indicated by increased expression of c-fos and pCREB after nerve ligation has been shown previously (Brightwell and Taylor, 2009; Martins et al, 2015). In further support of a facilitative function for ascending LC NA pathways during chronic neuropathic pain rather than the inhibitory function described in other acute pain models, we specifically performed pharmacological studies with NAα1 or NAα2 receptor antagonists to block NA signaling in the forebrain mPFC region.…”
Section: Discussionsupporting
confidence: 72%
“…Reducing noradrenaline release at the DRt by using a viral vector derived from the HSV-1 which selectively reduced noradrenaline synthesis in noradrenergic DRt afferents, significantly attenuated the behavioral manifestations of neuropathic pain for nearly 2 months (Martins et al, 2010). Our studies also show an impairment of the feedback inhibitory function of α 2 -adrenoreceptors at the DRt during neuropathic pain, which likely further contributes to enhance the noradrenergic input to the DRt during neuropathic pain (Martins et al, 2015b). The increased noradrenergic neurotransmission at the DRt, enhancing pain facilitation from this area, raises an important issue related to the treatment of neuropathic pain with antidepressants inhibiting noradrenaline reuptake.…”
Section: Chronic Pain As a Trigger Of Neuroplasticity At The Rvm-vlm-supporting
confidence: 56%
“…The recent studies performed by our group implicate the noradrenergic modulation of the DRt in the enhancement of DRt pain facilitation during neuropathic pain. We showed that nociceptive stimulation increased noradrenaline release at the DRt which enhanced pain facilitation from the DRt through activation of α 1 -adrenoreceptors (Martins et al, 2015b). Reducing noradrenaline release at the DRt by using a viral vector derived from the HSV-1 which selectively reduced noradrenaline synthesis in noradrenergic DRt afferents, significantly attenuated the behavioral manifestations of neuropathic pain for nearly 2 months (Martins et al, 2010).…”
Section: Chronic Pain As a Trigger Of Neuroplasticity At The Rvm-vlm-mentioning
confidence: 98%
See 1 more Smart Citation